Physical, psychological, and social experiences of women recovered from COVID-19 in Iran: A qualitative study - Vahideh Aghamohammadi; Fatemeh Rabiee-Khan; Khadijeh Nasiri; Aghil Habibi Soola; Yalda Mousazadeh; Hamed Rezakhani Moghaddam (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: This paper aims to examine the impact of COVID-19 on various health aspects of women recovered from this disease in Ardabil province, Iran. MATERIALS AND METHODS: This qualitative study using a content analysis approach was carried out through in-depth individual and focus group discussion using semi-structured interviews schedule in 26 women during June and August 2021. Interviews were recorded, transcribed, and MAXQDA six-stage analysis framework. RESULTS: Negative consequences of COVID-19 were generally categorized into five main themes (including increased self-conscious excitement, perceived social stigma, depression, changes in behavioral patterns, and reduced level of quality of life) and 13 subthemes. The positive consequences were the following five themes (including the development of the spiritual attitude, increasing the importance of personal health, the rise of perceived support, increased sense of altruism, and increased financial management) and four subthemes. CONCLUSION: Based on the findings, it is concluded that effective support by the government, society, and the medical staff could help to relieve people's psychological and social stress through providing financial aid, the right information, and training.